2019
DOI: 10.4414/smw.2019.20078
|View full text |Cite
|
Sign up to set email alerts
|

Solid cancer development in solid organ transplant recipients within the Swiss Transplant Cohort Study

Abstract: In solid organ transplant recipients (sOTRs), 5 years after transplantation cancer is a relevant cause of death. We aimed to report cancer incidence in the Swiss Transplant Cohort Study (STCS) between 2008 and 2014 and conducted a prospective cohort study of kidney, heart, lung, pancreas and liver transplant recipients enrolled into the STCS by retrospective analysis of collected data. The STCS provided data on 2758 solid organ transplants. In total, 134 cases of cancer were observed (30 liver, 21 prostate, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 17 publications
6
21
0
3
Order By: Relevance
“…The present data also showed significantly worse survival in the tumour-group, both after KT (Fig 3) and after tumour diagnosis (Fig 4). Similar to earlier investigations, mortality after tumour diagnosis was elevated [20,32]. However, the differences to matched PLOS ONE controls were mainly seen within the first years after diagnosis and mortality rates became similar later (Table 3; Fig 4).…”
Section: Risk Factors For the Development Of Cancer And Survival Aftesupporting
confidence: 88%
See 1 more Smart Citation
“…The present data also showed significantly worse survival in the tumour-group, both after KT (Fig 3) and after tumour diagnosis (Fig 4). Similar to earlier investigations, mortality after tumour diagnosis was elevated [20,32]. However, the differences to matched PLOS ONE controls were mainly seen within the first years after diagnosis and mortality rates became similar later (Table 3; Fig 4).…”
Section: Risk Factors For the Development Of Cancer And Survival Aftesupporting
confidence: 88%
“…Earlier studies explained this phenomena with the theory of dormant malignancies that are antedated and accelerated by the immunosuppression after KT [13]. This theory consequently leads to a lower mean of age at diagnosis and helps to explain the association between the time of observation and incidence of malignancies (Table 1) [2,13,16,20,31]. Moreover, malignancies after transplantation seem to correlate with a higher mortality, an excess risk of cancer-related death of over 2.5 times was shown after KT [2].…”
Section: Risk Factors For the Development Of Cancer And Survival Aftementioning
confidence: 92%
“…Our present results, based on 133 prostate cancer cases, agree well with the by far largest study of cancer incidence amongst solid transplant recipients (1039 prostate cancer cases) , with a meta‐analysis of six studies published before 2015 , and with a recent study from Australia and New Zealand (41 prostate cancer cases) . At odds with these and with our present study are two smaller studies: one Irish (34 prostate cancer cases) and one Swiss (18 prostate cancer cases), which reported a seven‐fold and a four‐fold higher prostate cancer incidence in kidney transplant recipients compared with the male population . One explanation for the raised incidence amongst Irish kidney transplant recipients is that they, in contrast with Irish men in general, were routinely offered PSA screening .…”
Section: Discussionsupporting
confidence: 89%
“…A large USA population‐based study showed a similar incidence of prostate cancer in solid organ transplant recipients as in the general population . Three other population‐based studies have been published: one from Australia and New Zealand showing similar results as the USA study , and one from Ireland and another from Switzerland, reporting a substantially increased prostate cancer incidence in male kidney transplant recipients . None of these studies differentiated between localised, low‐grade prostate cancer (that is most often detected after PSA testing) and advanced or high‐grade cancer (that is more likely to be lethal).…”
Section: Introductionmentioning
confidence: 97%
“…Data from the Swiss Transplant Cohort Study showed an increased incidence of PC in SOT patients, about three times the general Swiss population, however, this was not statistically significant for HT patients. 27 A study of 479 HT patients from the Finnish Cancer Registry showed a standardized incidence ratio (SMR) of 6 for all cancers in HT patients compared to the general Finnish population but no increase in the incidence of PC specifically. 28 Considering the available data, we suspect that the PC-specific mortality in a patient with very low or low-risk LPC undergoing HT to be exceedingly low, particularly if they are subsequently treated with definitive therapy (surgical prostatectomy or radiotherapy).…”
Section: Discussionmentioning
confidence: 99%